OPTIMALISASI PENERAPAN REGULASI PERBAIKAN ALAT KESEHATAN DAN STRATEGI PENGADAAN MENGGUNAKAN METODE KONTRAK PAYUNG DALAM MENINGKATKAN EFEKTIVITAS MANAGEMEN LOGISTIK DI RSUD GAMBIRAN KOTA KEDIRI - E, Agusta Dian; Z, Kholila Indana; Wiyati, Eni Rohma; Fauziyah; K, Hayumas Nurlita F (Jurnal Abdi Masyarakat, 2023)
The preparation of logistics for services in hospitals is very important because, without adequate logistics in terms of quantity, specification of goods, and accuracy of distribution, it is certain that services will be disrupted. In addition to preparing logistics, the logistics sector is responsible for implementing orderly administration in the logistics, equipment, and household sectors. The logistics sector prepares plans for the needs and procurement of logistics materials, compiles maintenance plans, compiles periodic reports on the condition of materials needed and installation equipment, and makes evaluations and suggestions regarding the use of materials/equipment and equipment (storage, management of materials or equipment and office inventory items) in all units in the hospital. This study aims to identify causes and provide solutions through effective strategies to improve logistics management at Gambiran Hospital, Kediri City. The method used is a fishbone diagram (Fishbone), USG method (Urgency, Seriousness, Growth), and SWOT analysis (Strength, Weakness, Opportunity, Threat). Based on the study results it was obtained to determine problems related to effective strategies to improve logistics management at Gambiran Hospital, Kediri City. The solutions proposed to overcome these problems are through optimizing regulations and strategies procurement in improving logistics management at Gambiran Hospital, Kediri City, in the form of implementing an MoU (Memorandum of Understanding) with third parties regarding the repair of equipment contained in the medical device maintenance service contract and implementing a logistics procurement strategy using the umbrella contract method.